Dyslipidemia in type 2 diabetes mellitus – a major risk factor for cardiovascular morbidity - Bobby D; Vinodha R (International Journal of Medical Research and Review, 2016)
Introduction: Diabetes mellitus is growing worldwide like an epidemic. Early identification of cardiovascular risk factors will decrease the morbidity in type 2 diabetes mellitus. This study was done to assess the prevalence of dyslipidemia among type 2 diabetic population.Methods: 40 cases of type 2 DM with duration of 8 to 12 yrs and 40 controls of both males and females in the age group of 40 to 65yrs were selected. Laboratory investigations like fasting glucose and lipid profile (fasting) were taken.Results: In the present study the levels of fasting glucose, total cholesterol, low density lipoproteins, triglycerides were high and the levels of high density lipoproteins were low in the type 2 diabetics compared to controls.Conclusion: Thus this study suggests the importance of early detection of dyslipidemia in type 2 diabetics mellitus and will reduce the prevalence of complications in diabetics.